2021
DOI: 10.1136/jmedgenet-2020-107459
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected role ofSIX1variants in craniosynostosis: expanding the phenotype ofSIX1-related disorders

Abstract: BackgroundPathogenic heterozygous SIX1 variants (predominantly missense) occur in branchio-otic syndrome (BOS), but an association with craniosynostosis has not been reported.MethodsWe investigated probands with craniosynostosis of unknown cause using whole exome/genome (n=628) or RNA (n=386) sequencing, and performed targeted resequencing of SIX1 in 615 additional patients. Expression of SIX1 protein in embryonic cranial sutures was examined in the Six1nLacZ/+ reporter mouse.ResultsFrom 1629 unrelated cases w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Mutations in SIX1 occur in the N-terminal protein-protein interaction domain (SD) or in the DNA-binding homeodomain (HD). A recent study also found Six1 mutations in patients with craniosynostosis and hearing defects (Calpena et al, 2021). Because Six1 has important roles in both normal and abnormal development of many tissues, we used Crispr/Cas 9 technology to create a null line in Xenopus tropicalis, an animal model highly suited for studying the cell and molecular regulation of gene function (Tandon et al 2017, Kakebeen and Wills 2019, Bhattacharya et al 2015.…”
Section: Combined Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in SIX1 occur in the N-terminal protein-protein interaction domain (SD) or in the DNA-binding homeodomain (HD). A recent study also found Six1 mutations in patients with craniosynostosis and hearing defects (Calpena et al, 2021). Because Six1 has important roles in both normal and abnormal development of many tissues, we used Crispr/Cas 9 technology to create a null line in Xenopus tropicalis, an animal model highly suited for studying the cell and molecular regulation of gene function (Tandon et al 2017, Kakebeen and Wills 2019, Bhattacharya et al 2015.…”
Section: Combined Results and Discussionmentioning
confidence: 99%
“…Since mutations in human SIX1 underlie some cases of BOR and craniosynostosis (Smith, 2018;Calpena et al, 2021), this line also will be very useful for elucidating the role of this gene in these craniofacial syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…This line of X. tropicalis will be a useful resource for the community seeking to elucidate the role of Six1 in the development of several tissues, including olfactory sensory epithelium, inner ear, cranial sensory ganglia, kidney, BAs, and somitic and hypaxial muscle. Since mutations in human SIX1 underlie some cases of BOR and craniosynostosis (Calpena et al, 2021;Smith, 2018), this line also will be very useful for elucidating the role of this gene in these craniofacial syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…the N-terminal protein-protein interaction domain (SD) or in the DNA-binding homeodomain (HD). A recent study also found Six1 mutations in patients with craniosynostosis and hearing defects (Calpena et al, 2021). Because Six1 has important roles in both normal and abnormal development of many tissues, we used Crispr/Cas9 technology to create a null line in Xenopus tropicalis, an animal model highly suited for studying the cell and molecular regulation of gene function (Bhattacharya, Marfo, Li, Lane, & Khokha, 2015;Kakebeen & Wills, 2019;Tandon, Conlon, Furlow, & Horb, 2017).…”
mentioning
confidence: 99%
“…Strengthening this argument are data from the murine knockout model that present with multiple anomalies including those related to the musculoskeletal system [ 61 , 66 ]. SIX1 has also been shown to segregate in birth defects related to bone development leading to excess bone formation [ 86 ]. Importantly, if manzamine-A use is suspected of affecting bone health, additional patient populations may be implicated including those susceptible to bone loss diseases.…”
Section: Introductionmentioning
confidence: 99%